2017
DOI: 10.16970/ted.80578
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory assessment for biological control of Tribolium confusum du Val., 1863 (Coleoptera: Tenebrionidae) by entomopathogenic fungi

Abstract: Laboratory assessment for biological control of Tribolium confusum du Val., 1863 (Coleoptera: Tenebrionidae) by entomopathogenic fungi Tribolium confusum du Val., 1863 (Coleoptera: Tenebrionidae)'un biyolojik mücadelesinde entomopatojen fungusların kullanımının laboratuvar ortamında değerlendirilmesi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…These percentages were significantly higher than the control (P<0.05) (Table 1). Komaki et al (2017) tested six entomopathogenic fungi isolates ((P. farinosus (2538), I. fumosorosea (4501), I. farinosa (3580), B. bassiana (4984), L. muscarium (972) and L. muscarium (5128)) against Tribolium confusum du Val., 1863 adults under laboratory conditions. In their study, these entomopathogenic fungi isolates led to the mortalities between 37.3 (for I. farinosa (3580) at 1×10 5 dose) and 100% (for P. farinosus (2538) and B. bassiana (4984) at 1×10 7 dose) on T. confusum adults after 10 days of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These percentages were significantly higher than the control (P<0.05) (Table 1). Komaki et al (2017) tested six entomopathogenic fungi isolates ((P. farinosus (2538), I. fumosorosea (4501), I. farinosa (3580), B. bassiana (4984), L. muscarium (972) and L. muscarium (5128)) against Tribolium confusum du Val., 1863 adults under laboratory conditions. In their study, these entomopathogenic fungi isolates led to the mortalities between 37.3 (for I. farinosa (3580) at 1×10 5 dose) and 100% (for P. farinosus (2538) and B. bassiana (4984) at 1×10 7 dose) on T. confusum adults after 10 days of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, entomopathogenic fungi could be a viable alternative method to control this pest. Up to now, there are many studies with the use of entomopathogenic fungi to control insect pests, but very little focused on using fungi as control agents against stored product pests (Ferroni 1977;Serale & Doberski 1984;Moina et al 1998;Sheeba et al 2001;Gökçe & Er 2005;Sevim et al 2010;Shifa Vanmathi et al 2011;Muştu et al 2014;Reddy et al 2014;Erler & Ateş 2015;Komaki et al 2017;Usanmaz Bozhüyük et al 2018;Bjornson & Elkabir 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers reported that the high efficacy levels recorded in their study indicate that the tested B. bassiana isolate could be effective biocontrol agent against S. oryzae. In another study by Komaki et al (2017), seven EPF isolates (B. bassiana (ARSEF-4984); Paecilomyces farinosus (ARSEF-2538); Isaria fumosorosea (ARSEF-4501); I. farinosa (ARSEF-3580); Lecanicillium muscarium (ARSEF-972 and ARSEF-5128), Mycotal extract of L. muscarium (as positive control) and distilled sterile water with Tween-20 (as negative control) were tested against T. confusum adults. All EPF isolates were sprayed at two different concentrations (1 × 10 5 and 1 × 10 7 conidia/ml) on adult insects in petri dishes.…”
Section: Discussionmentioning
confidence: 99%
“…Benzer bir araştırmada, Lecanicillium ve Isaria cinsine ait bazı entomopatojen fungus izolatlarının fasulye tohum böceğinin larva ve erginlerine karşı etkili olduğu saptanmıştır (Ondráčková, 2015). Komaki et al (2017)'ın yaptıkları bir çalışmada Lecanicillium muscarium, Isaria farinosa ve Isaria fumosorosea entomopatojen fungusları Tribolium confusum (Coleoptera: Tenebrionidae) erginlerine karşı etkili bulunmuşlardır. Baklagil tohumlarında bu zararlının değişik dönemlerine ve tohum ağırlığına Beauveria bassiana'nın etkili olmadığı rapor edilmiştir (Padin et al, 2002).…”
Section: Isaria Farinosaunclassified